Os direitos sociais em tempos de crise : a jurisprudência da crise no Brasil e em Portugal - Hendges, Carla Evelise Justino (2018)
The purpose of the study is to investigate the role of fundamental social rights in constitutionalism. For this, the applicability of social rights is investigated, in order to secure the best protection of social rights in in times of economic crisis and changes in society. Based on the premise of considerating social fundamental rights as a normative category, from which a theoretical basis for the understanding of social rights as fundamental rights is extracted, as well as to determine their applicability and extension of protection. Fundamental social rights are umbilically connected to the democratic principle and to the dignity of human person, being situated at the same level of importance and value as other rights, freedoms and guarantees. The level of protection of fundamental social rights in the national and international panorama, especially Portuguese and European, is investigated. The role of public authorities in the protection of fundamental social rights is of particular relevance. On the theme of (im) permanence of the Social State in times of crisis, there is tension between the situation of financial crisis and the protection of fundamental social rights. It is reflected on the limits and possibilities of social protection, seeking for such elements from the Portuguese and Brazilian experience of the ‘crisis jurisprudence’.